2023
DOI: 10.2196/39848
|View full text |Cite
|
Sign up to set email alerts
|

Digital Intergenerational Program to Reduce Loneliness and Social Isolation Among Older Adults: Realist Review

Abstract: Background There is a compelling need for an innovative and creative approach to promote social connectedness among older adults to optimize their well-being and quality of life. One possible solution may be through a digital intergenerational program. Objective This realist review aimed to identify existing digital intergenerational programs that were used to reduce loneliness or social isolation among older adults and analyze them in terms of strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…According to Anderson’s [ 80 ] research, older adults appreciated the challenge of playing against virtual trainers as well as the visual stimulus offered by games. This not only helps to focus attention on the enjoyment of electronic games but also gains the health benefits of PA. Phang's [ 81 ] study supports this finding by demonstrating that digital intergenerational programs can increase older adults' engagement and reduce loneliness.…”
Section: Discussionmentioning
confidence: 83%
“…According to Anderson’s [ 80 ] research, older adults appreciated the challenge of playing against virtual trainers as well as the visual stimulus offered by games. This not only helps to focus attention on the enjoyment of electronic games but also gains the health benefits of PA. Phang's [ 81 ] study supports this finding by demonstrating that digital intergenerational programs can increase older adults' engagement and reduce loneliness.…”
Section: Discussionmentioning
confidence: 83%
“…Although SI is a global epidemic implying the absence of meaningful human relations and social connectedness, befriending is a psychosocial tonic to building social relationships and intergenerational friendships [ 7 ] that might reduce boredom and depression and significantly enhance the quality of life among older adults [ 8 ] and youth. The feeling of companionship is augmented when an intergenerational conversation is conducted purposefully, thereby negating the exacerbating consequences of SI such as boredom or even the feeling of loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…SI is one of the most disruptive transformations that exacerbate the quality of life, affecting human behavior, perceptions, and experiences [ 10 , 15 ]. It is a condition that leaves one with feelings of boredom and loneliness that are detrimental to physical and mental health [ 7 ]. Loneliness among older adults is the subjective, distressed feeling of being alone or separated, whereas SI is the objective physical separation from the community [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This highlights the need for developing social, physical, and technological/digital intergenerational services, spaces, and places that not only accommodate older adults but that welcome them as an integral part of everyday community life. Moreover, research has shown that intergenerational interventions can improve cognitive, emotional, and physical outcomes for both older and younger participants, as well as promote positive attitudes towards aging and reduce ageism and stereotypes [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%